Valley filtering in graphene due to substrate-induced mass potential. (24th April 2017) - da Costa, D R; Chaves, A; Farias, G A; Peeters, F M
Abstract: The interaction of monolayer graphene with specific substrates may break its sublattice symmetry and results in unidirectional chiral states with opposite group velocities in the different Dirac cones (Zarenia et al 2012 Phys. Rev . B86 085451). Taking advantage of this feature, we propose a valley filter based on a transversal mass kink for low energy electrons in graphene, which is obtained by assuming a defect region in the substrate that provides a change in the sign of the substrate-induced mass and thus creates a non-biased channel, perpendicular to the kink, for electron motion. By solving the time-dependent Schrödinger equation for the tight-binding Hamiltonian, we investigate the time evolution of a Gaussian wave packet propagating through such a system and obtain the transport properties of this graphene-based substrate-induced quantum point contact. Our results demonstrate that efficient valley filtering can be obtained, provided: (i) the electron energy is sufficiently low, i.e. with electrons belonging mostly to the lowest sub-band of the channel, and (ii) the channel length (width) is sufficiently long (narrow). Moreover, even though the transmission probabilities for each valley are significantly affected by impurities and defects in the channel region, the valley polarization in this system is shown to be robust against their presence.